Coupled-channels analysis of the (51Σu+, 51Πu, 53Πu, 23Δu) complex of electronic states in rubidium dimer. (December 2018) - Pashov, A.; Kowalczyk, P.; Grochola, A.; Szczepkowski, J.; Jastrzebski, W.
Highlights: Global deperturbation analysis. Coupled channels treatment of perturbed molecular states with spectroscopic accuracy. Highly excited electronic states. Abstract: We present a study of the 5 1 Σ u + and 5 1 Πu electronic states in Rb2 strongly coupled with each other and with the surrounding triplet states. Energies of more than 8000 rovibrational levels of the mutually interacting manifold of states were measured by polarization labelling spectroscopy technique. A deperturbation was performed by coupled-channels analysis involving also the 5 3 Πu and 2 3 Δu states and taking into account both spin-orbit and rotational perturbations. Energies of nearly 99% observed levels in two isotopologues 85 Rb2 and 85 Rb 87 Rb were reproduced with a standard deviation of 0.08 cm − 1, consistent with the experimental accuracy. Potential energy curves of the four involved electronic states and R -dependent perturbation matrix elements were determined and compared with the most recent theoretical predictions, whenever available.